Spatiotemporal analysis and mapping of LULC changes and thermal environment variations in Al Khobar, Saudi Arabia using remote sensing techniques - Faqeih, Khadeijah Yahya; Alamri, Somayah Moshrif; Alamery, Eman Rafi; Aldubehi, Maha Abdullah; Al-Khalil, Omar Mohammed; Fadl, Mohamed E. (Frontiers in Environmental Science, 2025)
IntroductionThis study investigates the relationship between land use/land cover (LULC) changes and land surface temperature (LST) dynamics in Al-Khobar, Saudi Arabia, a rapidly urbanizing desert city, from 1999 to 2024. The research addresses the critical need to understand urban thermal environment changes driven by anthropogenic modification in arid regions.MethodsThe analysis utilized Landsat satellite imagery. LULC changes were quantified using post-classification comparison and spectral indices, including the Normalized Difference Vegetation Index (NDVI), Normalized Difference Built-up Index (NDBI), Normalized Difference Water Index (NDWI), and Barren Soil Index (BSI). LST was retrieved using a radiative transfer equation. Statistical correlation analyses were performed to examine the relationships between these spectral indices and LST for the study years.ResultsSignificant LULC transformations were observed: urban area increased by 71.5%, while barren land decreased by 50.6%. Vegetation cover grew by 12.4%, and water bodies shrank by 20.1%. Concurrently, the average LST rose from 40.2°C to 42.5°C. Correlation analyses revealed: 1) a strong positive correlation between NDBI and LST, with NDBI increasing from 0.395 to 0.635; 2) a consistent positive correlation between NDVI and LST, challenging the typical cooling paradigm; 3) a strong negative correlation between NDWI and LST, with NDWI declining from 0.518 to 0.294; and 4) a negative correlation between BSI and LST, with BSI decreasing from 0.374 to 0.267.DiscussionThe results identify urban expansion (indicated by NDBI) as the primary driver of surface heating. The positive NDVI-LST correlation suggests that the cooling efficacy of irrigated urban greenery in arid settings can be compromised by the surrounding heat-retaining built-up matrix. The strong negative NDWI-LST correlation underscores the disproportionate cooling importance of water bodies, whose decline contributed to warming. The findings provide an evidence-based refinement of LULC-LST dynamics for arid environments, concluding that sustainable urban planning in desert cities must prioritize water body conservation, mandate high-albedo materials, and re-evaluate greening strategies based on proven cooling efficacy rather than mere area coverage.